A Communication Delay Compensation Method Applied to ACLs for Distributed Energy Consumption. (July 2018) - Zhang, Xinyi; Jiang, Limin; Li, Kecheng; Hu, Congchuan; Ma, Xiaoming; Zhou, Bowen
Abstract: With the development of smart power systems, it has become possible to adjust the operating status of aggregated air conditioning loads (ACLs) to make them trace the commands for distributed energy sources consumption. However, inevitable communication delay causes conspicuous control error. On the basis of analyzing control error of ACLs caused by communication delay, this paper proposes a communication delay compensation method based on network predictive control system. Then, aggregated ACLs are applied to consume the distributed energy sources in a microgrid, and several simulations demonstrate the compensation method proposed in this paper. The simulation results show that this method can diminish the control error caused by random communication delay to a large extent.